Association of depressive symptoms with incidence and mortality rates of COVID-19 over 2 years among healthcare workers in 20 countries: multi-country serial cross-sectional study - Asaoka, Hiroki; Watanabe, Kazuhiro; Miyamoto, Yuki; Restrepo-Henao, Alexandra; van der Ven, Els; Moro, Maria Francesca; Alnasser, Lubna A; Ayinde, Olatunde; Balalian, Arin A; Basagoitia, Armando; Durand-Arias, Sol; Eskin, Mehmet; et al. (BMC medicine, 2024)
BACKGROUND: Long-term deterioration in the mental health of healthcare workers (HCWs) has been reported during and after the COVID-19 pandemic. Determining the impact of COVID-19 incidence and mortality rates on the mental health of HCWs is essential to prepare for potential new pandemics. This study aimed to investigate the association of COVID-19 incidence and mortality rates with depressive symptoms over 2 years among HCWs in 20 countries during and after the COVID-19 pandemic. METHODS: This was a multi-country serial cross-sectional study using data from the first and second survey waves of the COVID-19 HEalth caRe wOrkErS (HEROES) global study. The HEROES study prospectively collected data from HCWs at various health facilities. The target population included HCWs with both clinical and non-clinical roles. In most countries, healthcare centers were recruited based on convenience sampling. As an independent variable, daily COVID-19 incidence and mortality rates were calculated using confirmed cases and deaths reported by Johns Hopkins University. These rates represent the average for the 7 days preceding the participants' response date. The primary outcome was depressive symptoms, assessed by the Patient Health Questionnaire-9. A multilevel linear mixed model (LMM) was conducted to investigate the association of depressive symptoms with the average incidence and mortality rates. RESULTS: A total of 32,223 responses from the participants who responded to all measures used in this study on either the first or second survey, and on both the first and second surveys in 20 countries were included in the analysis. The mean age was 40.1 (SD = 11.1), and 23,619 responses (73.3%) were from females. The 9323 responses (28.9%) were nurses and 9119 (28.3%) were physicians. LMM showed that the incidence rate was significantly and positively associated with depressive symptoms (coefficient = 0.008, standard error 0.003, p = 0.003). The mortality rate was significantly and positively associated with depressive symptoms (coefficient = 0.049, se = 0.020, p = 0.017). CONCLUSIONS: This is the first study to show an association between COVID-19 incidence and mortality rates with depressive symptoms among HCWs during the first 2 years of the outbreak in multiple countries. This study's findings indicate that additional mental health support for HCWs was needed when the COVID-19 incidence and mortality rates increase during and after the early phase of the pandemic, and these findings may apply to future pandemics. TRIAL REGISTRATION: Clinicaltrials.gov, NCT04352634.
Keywords: dospělí; Multi-country study; Health Personnel; Female; SARS-CoV-2; Adult; ženské pohlaví; zdravotnický personál; průřezové studie; Depressive symptoms; lidé; COVID-19; Serial cross-sectional study; Incidence; Cross-Sectional Studies; Male; incidence; lidé středního věku; deprese; Mortality rate; mužské pohlaví; Depression; Healthcare worker; Middle Aged; Incidence rate; Humans